HUBUNGAN ANTARA PENGETAHUAN DAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA INSTALASI LISTRIK DI PT XYZ - Dharma Utama Mataram, I Ketut Mahesa; Priambadi, I Gusti Ngurah; Sinta Setiawati, NLP Lilis; Kade Suriadi, I Gusti Agung; Sista Dewi, Desak Ayu; Imanuel Sitanggang, Bryan Estavan; Mataram, I Made (Jurnal SPEKTRUM; Vol 12 No 2 (2025): Jurnal SPEKTRUM, 2025)
This study aims to examine the relationship between knowledge and compliance in the use of personal protective equipment (PPE) among electrical installation workers at PT. XYZ. Although workers have a fundamental understanding of the importance of PPE, preliminary findings indicate a low compliance rate. A cross-sectional quantitative design was employed, wherein the knowledge and compliance variables were measured through a validated and reliable questionnaire. Bivariate analysis using the Chi-Square test showed a significant relationship between knowledge and the compliance of PPE usage. Based on the results, program recommendations are proposed to enhance the awareness and proper use of PPE in order to reduce occupational accident risks.